TRUST IN B2B E-MARKETPLACES - SEBASTIAN KOT; JANUSZ K. GRABARA; MIHAELA SANDU; MARCELA MIHĂILESCU (Annals of the University of Petrosani: Economics)
The paper presents background of B2B exchanges and review of their forms and functionalities. The benefits and fails reasons are noticed. European enterprises interest in B2B trade is next aspect of consideration. Finally, the trust barriers of B2B exchanges are presented.